Precursor Duration and Thermal Annealing Effects in InGaN/GaN Multiple Quantum Wells Grown on Nitrogen-Polar GaN Templates by a Pulsed Metallorganic Chemical Vapor Deposition. (15th September 2018) - Feng, Shih-Wei; You, Yu-Siang; Huang, Chien-Jung; Wang, Hsiang-Chen; Tu, Li-Wei; Song, Jie; Han, Jung
Abstract : In this study, the effects of precursor duration and thermal annealing on the material and optical properties of InGaN/GaN multiple quantum wells (MQWs) grown on nitrogen (N) -polar GaN templates by a pulsed metallorganic chemical vapor deposition are investigated. With a 2-sec NH3 precursor duration, an apparent indium aggregation leads to a higher density and larger size of InGaN mounds for more exciton accumulation, enhancing the radiative recombination and luminescence efficiency. In addition, the more, larger, and brighter light spots in the cathodoluminescence (CL) images and a stronger CL intensity in the annealed sample show that a smaller size and higher density of InGaN mounds enhance the radiative recombination and luminescence efficiency. Both a 2-sec NH3 precursor duration and 60-sec thermal annealing are beneficial to the growth conditions of InGaN/GaN MQWs grown on N -polar GaN templates. The research results of the pulsed growth mode provide important information to optimize growth conditions of InGaN/GaN MQWs grown on N -polar GaN templates.